A study of negative emotion, perception of fairness and work attitude in the context of performance management system among the Malaysian general workers - Hoh, Chin Chin (2021)
This thesis describes the research work examining the emotional responses to performance management (PM) processes as the predictors of work attitudes in a Malaysian context. The workers’ perceptions of fairness are also tested for their mediation effects in this relationship. Building on the Affective Event Theory (AET) and the theory of organisational justice, two models are derived to understand the relationships among the chosen constructs.